2015
DOI: 10.1073/pnas.1419335112
|View full text |Cite
|
Sign up to set email alerts
|

Gait and speed selection in slender inertial swimmers

Abstract: Inertial swimmers use flexural movements to push water and generate thrust. We quantify this dynamical process for a slender body in a fluid by accounting for passive elasticity and hydrodynamics and active muscular force generation and proprioception. Our coupled elastohydrodynamic model takes the form of a nonlinear eigenvalue problem for the swimming speed and locomotion gait. The solution of this problem shows that swimmers use quantized resonant interactions with the fluid environment to enhance speed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 35 publications
2
59
0
Order By: Relevance
“…For elastic plates forced by an oscillating torque distribution, the highest velocities are also observed near the resonant frequency forcing. 21 Data collected from natural swimmers show that the swimming characteristics in the turbulent regime, i.e., a Reynolds number Re larger than 3000, 22 are governed by the relative uniformity of two dimensionless numbers, the Strouhal number St = Af /U 0 ∼ 0.3 [22][23][24][25][26][27] and the ratio A/L ∼ 0.2, [26][27][28][29] with swimming velocity U 0 , fish length L, tailbeat amplitude A, and frequency f. To understand these data in terms of swimming efficiency, numerous Refs. 4-7, 10, and 30-34 have assumed that the mean thrust F T scales with the dynamic pressure and that the thrust coefficient should be defined as F T / 1 2 ρS T U 2 0 , where ρ is the fluid density and a) Author to whom correspondence should be addressed: mederic.argentina@ unice.fr S T is the effective propulsive area of the fish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For elastic plates forced by an oscillating torque distribution, the highest velocities are also observed near the resonant frequency forcing. 21 Data collected from natural swimmers show that the swimming characteristics in the turbulent regime, i.e., a Reynolds number Re larger than 3000, 22 are governed by the relative uniformity of two dimensionless numbers, the Strouhal number St = Af /U 0 ∼ 0.3 [22][23][24][25][26][27] and the ratio A/L ∼ 0.2, [26][27][28][29] with swimming velocity U 0 , fish length L, tailbeat amplitude A, and frequency f. To understand these data in terms of swimming efficiency, numerous Refs. 4-7, 10, and 30-34 have assumed that the mean thrust F T scales with the dynamic pressure and that the thrust coefficient should be defined as F T / 1 2 ρS T U 2 0 , where ρ is the fluid density and a) Author to whom correspondence should be addressed: mederic.argentina@ unice.fr S T is the effective propulsive area of the fish.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that in the laminar regime (Reynolds number smaller than 3000), the relevant dimensionless parameter changes due to a change in the drag expression to account for the viscous boundary layer. Actually a subtle hypothesis is hidden behind this simple balance: 21 to the leading order, thrust and drag can be treated separately, with thrust mostly independent of the swimming velocity 11,21,35 and drag mostly independent of the fin frequency or amplitude. 21 It is remarkable that this idea was already in the mind of Lighthill 8 and that his definition of the thrust coefficient C T seems to be the natural one, 9,36…”
Section: Introductionmentioning
confidence: 99%
“…Borazjani & Sotiropoulos 2010;van Rees et al 2013van Rees et al , 2015Li et al 2016). It should be noted that the nonlinear character of this resistive term sets it apart from the viscous dissipation that has been included in other models of similar problems (Argentina & Mahadevan 2005;Gazzola et al 2015). Concerning artificial elastic swimmers with localised actuation, Ramananarivo, Godoy-Diana & Thiria (2014a) showed that the resistive term is determinant for the establishment of the propagative wave that mimics the kinematics of animal swimmers, and Paraz et al (2016) have incorporated it in a successful model predicting thrust generation of a heaving foil.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by histological analysis (fig. S1) as well as theoretical considerations (26), we channeled muscular work and elastic energy into forward motion by breaking fore-aft symmetry through a varying body rigidity along the anterior-posterior axis. This was achieved via a thicker body, and a denser and radially further reaching skeleton pattern in the front (Fig.…”
mentioning
confidence: 99%